Evaluation of the Diagnostic Performance of Physical Examination Combined with Transvaginal Ultrasonography in Patients with Endometriosis - Talha Tiryaki; Tolga Karacan; Seyma Yesiralioglu; Eser Ozyurek; Huseyin Kiyak; Engin Oral (Medical Network, 2020)
Objective: Owing to its high sensitivity and specificity, and because it is widely available, transvaginal ultrasonography is the first-line imaging test of choice used for the diagnosis of endometriosis. Ultrasonographic findings evaluated in conjunction with symptoms and signs may improve the diagnosis of endometriosis. Therefore, we hypothesized that transvaginal ultrasonography combined with physical examinations performed by physicians could predict endometriosis better in patients with symptoms suggestive of endometriosis compared with asymptomatic patients at presentation. Study Design: In this retrospective cohort study, the first subjective impression obtained from the history, physical examination, and transvaginal ultrasonography performed by the physician during the first visit in the outpatient clinic was taken into consideration. Patients who underwent surgery with the indication of ovarian mass were divided into two groups according to their admission types; symptomatic and asymptomatic. Results: The number of patients reported to have endometriosis histopathologically was 138;132 were in the premenopausal period (symptomatic group n=101, asymptomatic group n=31) and 6 were in the postmenopausal period (symptomatic group n=1, asymptomatic group n=5). The positive predictive value and positive likelihood ratio of the combination of pelvic examination and transvaginal ultrasonography in premenopausal symptomatic and asymptomatic patients, and postmenopausal symptomatic and asymptomatic patients were 97.8%, 11.5; 47.3%, 6.9; 25.0%, 4.6; and 11.1%, 2.3, respectively. Conclusion: The diagnostic performance of transvaginal ultrasonography in combination with physical examination in patients with asymptomatic endometriosis cannot reach the diagnostic accuracy of physical examination combined with transvaginal ultrasonography in patients with endometriosis who present with symptoms.